Reorganization free energy of copper proteins in solution, in vacuum, and on metal surfaces - Kontkanen, Outi Vilhelmiina; Biriukov, Denys; Futera, Zdenek (The Journal of chemical physics, 2022)
Metalloproteins, known to efficiently transfer electronic charge in biological systems, recently found their utilization in nanobiotechnological devices where the protein is placed into direct contact with metal surfaces. The feasibility of oxidation/reduction of the protein redox sites is affected by the reorganization free energies, one of the key parameters determining the transfer rates. While their values have been measured and computed for proteins in their native environments, i.e., in aqueous solution, the reorganization free energies of dry proteins or proteins adsorbed to metal surfaces remain unknown. Here, we investigate the redox properties of blue copper protein azurin, a prototypical redox-active metalloprotein previously probed by various experimental techniques both in solution and on metal/vacuum interfaces. We used a hybrid quantum mechanical/molecular mechanical computational technique based on density functional theory to explore protein dynamics, flexibility, and corresponding reorganization free energies in aqueous solution, vacuum, and on vacuum gold interfaces. Surprisingly, the reorganization free energy only slightly decreases when azurin is dried because the loss of the hydration shell leads to larger flexibility of the protein near its redox site. At the vacuum gold surfaces, the energetics of the structure relaxation depends on the adsorption geometry; however, significant reduction of the reorganization free energy was not observed. These findings have important consequences for the charge transport mechanism in vacuum devices, showing that the free energy barriers for protein oxidation remain significant even under ultra-high vacuum conditions.
Keywords: zlato; měď; Copper; voda; Metalloproteins; Vacuum; oxidace-redukce; Gold; Water; azurin; metaloproteiny; Oxidation-Reduction; Azurin; vakuum; Electron Transport; transport elektronů